Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
To simplify the given expression [tex]\(2x^2 - 4x + 5 - \frac{1}{3}(x^2 - 5x + 7)\)[/tex], follow these steps:
1. Distribute the [tex]\(\frac{1}{3}\)[/tex] across the terms inside the parenthesis:
[tex]\[ \frac{1}{3}(x^2 - 5x + 7) = \frac{1}{3}x^2 - \frac{5}{3}x + \frac{7}{3} \][/tex]
2. Rewrite the expression by including the distributed terms:
[tex]\[ 2x^2 - 4x + 5 - \left( \frac{1}{3}x^2 - \frac{5}{3}x + \frac{7}{3} \right) \][/tex]
3. Distribute the negative sign across the terms inside the parenthesis:
[tex]\[ 2x^2 - 4x + 5 - \frac{1}{3}x^2 + \frac{5}{3}x - \frac{7}{3} \][/tex]
4. Combine like terms:
- For [tex]\(x^2\)[/tex] terms:
[tex]\[ 2x^2 - \frac{1}{3}x^2 = \left(2 - \frac{1}{3}\right)x^2 = \frac{6}{3}x^2 - \frac{1}{3}x^2 = \frac{5}{3}x^2 = 1.66666666666667x^2 \][/tex]
- For [tex]\(x\)[/tex] terms:
[tex]\[ -4x + \frac{5}{3}x = -\frac{12}{3}x + \frac{5}{3}x = \left(-4 + \frac{5}{3}\right)x = -\left(4 - \frac{5}{3}\right)x = -\left(\frac{12}{3} - \frac{5}{3}\right)x = -\frac{7}{3}x = -2.33333333333333x \][/tex]
- For constant terms:
[tex]\[ 5 - \frac{7}{3} = \frac{15}{3} - \frac{7}{3} = \frac{8}{3} = 2.66666666666667 \][/tex]
5. Write down the simplified expression by combining all the simplified terms:
[tex]\[ 1.66666666666667x^2 - 2.33333333333333x + 2.66666666666667 \][/tex]
Thus, the simplified form of the given expression is:
[tex]\[ 1.66666666666667x^2 - 2.33333333333333x + 2.66666666666667 \][/tex]
1. Distribute the [tex]\(\frac{1}{3}\)[/tex] across the terms inside the parenthesis:
[tex]\[ \frac{1}{3}(x^2 - 5x + 7) = \frac{1}{3}x^2 - \frac{5}{3}x + \frac{7}{3} \][/tex]
2. Rewrite the expression by including the distributed terms:
[tex]\[ 2x^2 - 4x + 5 - \left( \frac{1}{3}x^2 - \frac{5}{3}x + \frac{7}{3} \right) \][/tex]
3. Distribute the negative sign across the terms inside the parenthesis:
[tex]\[ 2x^2 - 4x + 5 - \frac{1}{3}x^2 + \frac{5}{3}x - \frac{7}{3} \][/tex]
4. Combine like terms:
- For [tex]\(x^2\)[/tex] terms:
[tex]\[ 2x^2 - \frac{1}{3}x^2 = \left(2 - \frac{1}{3}\right)x^2 = \frac{6}{3}x^2 - \frac{1}{3}x^2 = \frac{5}{3}x^2 = 1.66666666666667x^2 \][/tex]
- For [tex]\(x\)[/tex] terms:
[tex]\[ -4x + \frac{5}{3}x = -\frac{12}{3}x + \frac{5}{3}x = \left(-4 + \frac{5}{3}\right)x = -\left(4 - \frac{5}{3}\right)x = -\left(\frac{12}{3} - \frac{5}{3}\right)x = -\frac{7}{3}x = -2.33333333333333x \][/tex]
- For constant terms:
[tex]\[ 5 - \frac{7}{3} = \frac{15}{3} - \frac{7}{3} = \frac{8}{3} = 2.66666666666667 \][/tex]
5. Write down the simplified expression by combining all the simplified terms:
[tex]\[ 1.66666666666667x^2 - 2.33333333333333x + 2.66666666666667 \][/tex]
Thus, the simplified form of the given expression is:
[tex]\[ 1.66666666666667x^2 - 2.33333333333333x + 2.66666666666667 \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.